2020
DOI: 10.1039/d0se00839g
|View full text |Cite
|
Sign up to set email alerts
|

Pt/CuSe: a new counter electrode for polyiodide reduction in quantum dot-sensitized solar cells

Abstract: The most common structure of a quantum dot-sensitized solar cell (QDSC) employs a metal sulfide counter electrode (CE) combined with a polysulfide electrolyte (S^(2-)/S_n^(2-)). Polyiodide electrolytes (I^-/I_3^-) have an advantage...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Although the maximum PCE of our device is higher or comparable to that of some reported works [37,38], the PCE value is still relative low when compared with the high-performance QDSSC (4%-5%) (table 1) [39][40][41][42][43]. The phenomenon can be attributed to the following reasons.…”
Section: Resultssupporting
confidence: 46%
See 3 more Smart Citations
“…Although the maximum PCE of our device is higher or comparable to that of some reported works [37,38], the PCE value is still relative low when compared with the high-performance QDSSC (4%-5%) (table 1) [39][40][41][42][43]. The phenomenon can be attributed to the following reasons.…”
Section: Resultssupporting
confidence: 46%
“…The phenomenon can be attributed to the following reasons. For one thing, the copper selenide CEs with high catalytic activity are usually composed of nanosheets/nanoflakes or composited with other materials, such as Pt [39], MXene [40], Cu x S [41], graphene [43]. The two-dimensional structure of nanosheets/nanoflakes could provide higher surface density of catalytic active sites exposed to the polysulfide electrolyte, which result in the great decrease in charge transfer resistance and the enhancement of electrochemical catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The counter electrode (CE) is an essential component in QDSSCs for the following reasons: 1) it catalyzes the reduction reaction of the oxidized species present in the electrolyte, 2) collects electrons from the electrical circuit and transfers them to the electrolyte, thus promoting the reduction of oxidized species, 3) ensures the flow of electrons in the photoelectrochemical solar cell [117][118][119] Therefore, the CE must have high catalytic activity in the electrolyte used in the QDSSCs, high electrical conductivity, good adhesion to the substrate, low cost, and high stability. [120][121][122] Early in the development of the QDSSCs it was observed that most chalcogenide QDs were unstable in the iodide/triiodide electrolyte. [39] Consequently, this electrolyte was replaced by polysulfide, which has good compatibility with most investigated QDs, leading to a considerable increase in the efficiency of such solar cells.…”
Section: Ces In Qdsscsmentioning
confidence: 99%